Effect of garlic extract, ascorbic acid and nicotinamide on growth, some biochemical aspects, yield and its components of three faba bean (Vicia faba L.) cultivars under sandy soil conditions - Mohamed, Magda H. (2021)
The obtained results showed that Nubaria-1 was superior to Nubaria-2 and Giza-843 in all growth and yield criteria in the growing seasons except plant height was superior in Nubaria-2. Foliar treatment of garlic extract had the superiority effect in all characters of growth and yield and its components, and consequently increased significantly all yield criteria of Nubaria-1 cultivar. Data clearly showed that the effect of different treatments caused marked increases in photosynthetic pigments, indole acetic acid, phenolics, carbohydrate constituents, free amino acids and proline contents of Nubaria 1 cultivar which was sprayed by garlic extract at 5% followed by nicotinamide and ascorbic acid, respectively.